Interpersonal Dynamics in 2-vs-1 Contexts of Football: The Effects of Field Location and Player Roles - Laakso, Timo; Davids, Keith; Liukkonen, Jarmo; Travassos, Bruno (Frontiers in Psychology, 2019)
This study analyzed the spatial-temporal interactions that sustained 2 vs 1 contexts in football at different field locations near the goal. Fifteen male players (under 15 yrs), 5 defenders, 7 midfielders and 3 attackers, participated in the study. Each participant performed a game to simulate a 2 vs 1 sub-phase as a ball carrier, 2nd attacker and defender at three different field locations, resulting in a total number of 142 trials. The movements of participants in each trial were recorded and digitized with TACTO software. Values of interpersonal distance between the ball carrier and defender and interpersonal angles between players and between the goal target, defender and ball carrier were calculated. The results revealed a general strong effect of field location. According to changes in designated field zones of performance, the relationship between values of interpersonal distances and relative angles between players and the goal revealed different relational dynamics. Related with participants’ roles, defenders revealed subtle differences as attackers on interpersonal distances and relative angles compared with midfielders and attackers. Our findings supported that field location is a key constraint of performance and that player's team role constraint performance effectiveness in football.